Teachers’ Practices in Using Educational Mobile Applications to Teach English - Aryani, Oktianti Dwi; Linggar Bharati, Dwi Anggani; Astuti, Puji (English Education Journal, 2021)
English language learning has shifted with the development of technology in education. Learning can also be done through easy access from a mobile phone. Educational mobile applications bridge the teaching learning processes effectively. This study aims to investigate the teachers’ practices in using educational mobile applications to teach English in senior high school in Semarang. This study utilize case study approach to achieve the objectives of the study. Questionnaire, interview, document analysis, and classroom observation were applied to investigate the teachers’ practices in using educational mobile applications in relation to multimedia learning theory and the Technological Pedagogical Content Knowledge (TPACK) theory. An evaluation rubric was used to find out the effectiveness of the educational mobile applications the participants used in teaching. Then a compatibility checklist was used to find out the compatibility of the educational mobile applications with the current curriculum, the 2013 curriculum. The findings revealed that the teachers were aware of multimedia learning when they chose to use certain educational mobile applications to teach English. They also possessed what the TPACK suggested. Therefore, they had the tools they needed to integrate technology into their classrooms. The study showed that from the five educational mobile applications the teachers used, Google Classroom was the most effective, whereas Goggle Drive was the least effective. The other three, 360 Video, YouTube, and Google Slides could, meanwhile, be considered effective apps. In case of compatibility of the educational mobile apps with the 2013 curriculum, it could be said that all of the educational mobile applications were compatible with the curriculum since they were applicable in classroom settings.